Content Analysis of Local Culture Representation in the ‘English for Nusantara’ Textbook for Secondary School - Fitri, Wahidatul; Risnawati, Risnawati; Febriani, Hanura (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study analyzes the representation of local Indonesian culture in the English for Nusantara textbook series for Junior High School. Employing a mixed-methods approach with a convergent parallel design, data were analyzed using the cultural frameworks of Cortazzi and Jin (1999) and Yuen (2011). The findings reveal a strong dominance of local culture (Source Culture) with an average representation of 72.48%, while target culture (Target Culture) constitutes only 4.79%. The representation of local culture develops strategically across grade levels: serving as a familiar scaffold in Grade VII, a tool for civic education in Grade VIII, and a platform for global agency in Grade IX. These findings reflect a “Local-Centric with Strategic Global Awareness” model, aligning with the English as an International Language (EIL) paradigm and the glocalization objectives of the Merdeka Curriculum. The study concludes that the textbook series successfully repositions English as a tool for local expression and global engagement, detached from Western cultural hegemony.